Peran Bi’ah Lughawiyyah dalam Meningkatkan Pemerolehan Bahasa Arab - M. Rizal Rizqi (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2016)
Bi'ah Lughawiyyah is Arabic language environment in which a person interacting with others using the Arabic language as a communication tool. Bi'ah Lughawiyyah is the main facility for students in acquiring first and second languages. The student's first language is the mother tongue derived from birth to adulthood while their second language is Arabic obtained through bi'ah lughawiyyah. Lughawiyyah Bi'ah is very important in realizing the speaking skills for everyday communication. With the Bi'ah Lughawiyah, the very spirit and happy students in obtaining Arabic because with Bi'ah Lughawiyyah they felt as if they were living in the Middle East region so that a spirit of dialogue by using Arabic is quite high even if they are shy do not speak Arabic. Bi'ah Lughawiyyah can be obtained formally or informally on the level of education.role Bi'ah Lughawiyyah very effective in enhancing the Arabic language acquisition supported by strategies and media in line with expectations that can provide maximum results in the Arabic language acquisition